Case study on deformation control of upper-soft and lower-hard large span tunnel station using combined control technology and monitoring demonstration - Shang, Yanliang; Du, Shouji; Han, Tongyin; Shao, Biao (Penerbit Universiti Kebangsaan Malaysia, 2017)
A large number of shallow buried tunnels are built in the city nowadays and the special strata such as large upper-soft and lower-hard ground often encountered. Deformation control of strata is the focus issue related to the construction safety. Based on Dalian metro Hing Street station with the classical geological condition of upper-soft and lower-hard ground, this paper fully used a combined control method including six different support measures to control the deformation of surrounding rock. 3D finite element model was setup to analyze the construction effect of combined control measures and the monitoring in-site was carried out to verify the deformation control effect of combined control method. It shows that the maximum surface subsidence value is gradually reduced with the support measures gradually increasing. In the case of various supports the maximum sedimentation value is 2.67 cm, which is 42. 1% lower than that of not using control method and the control effect is obvious. In addition, it can be seen that the two-layer initial support and additional large arch foot have the best effect on controlling the ground surface settlement with reduction of 11.7% and 20.2%, respectively. The research results can provide practical experience for the construction of such tunnels, and guide the design and construction of the tunnel in the future.